The Study Factor of Online Resources with Learning on the Selection of Secondary School Students with Different Cognitive Learner Style - Thongkred, Chetthapol; Intakanok, Prachit; Sanguansat, Kajohnsak; Bunked, Nootjaree (วารสารพิชญทรรศน์, 2018)
This research aimed to study the factor of online resources with learning on the selection of secondary school students with different cognitive learner style. The sample groups of this study were 140 secondary school students; field independent was 75 people and field dependent were 65 people. Learning management plan, e-learning achievement test, the student interview, a survey of the factor of online resources with learning e-learning, data collecting form, cognitive assessment form, student’s manual and teacher’s manual are the research tools. Statistics used in data analysis were frequency, distribution percentage, mean, analysis hypothesis testing with t-test and analysis of variance. The research results were as follows, 1. The students choose social media because there are animations, sounds, entertainment, knowledge and chatting to exchange information. Therefore, they aren’t bored to learn. They always used search engine in every day. It was familiar, memorable, easy access, quick and easy to use. Moreover, many organizations provide (www.) to support their specific targets so, when you need to search, you can use it. 2. The most factors field independent group used were familiarity factor; familiar, knowledge, used in every day, usability factor, can copy file to use in public relations, for teaching and depend on the service factor, technology equipment, searching programs, the tools help for use in shot-time and students in Field Dependent group used in service factor, searching programs, use in short-time, fast to access the information, Usability factor, can copy files to publicize and the sequence factor, the top of sequence were chose the first to use and it wasn’t waste the time for search. 3. The standard deviation and the mean of pre-test score field independent and field dependent group, they were different classifier of cognitive learner style and different pre-test score with the significance level of 0.05. The standard deviation, the mean of post-test score in field independent and field dependent group, they were classifier different of cognitive learner style and different post-test score with the significance level of 0.05